Why is Gender Based Violence still Prevalent at Secondary Schools in Morogoro Region, Tanzania? - Kinemo, Stella Malangalila (Journal of Policy and Leadership, 2018)
Bearing the obstacles of Gender Based Violence (GBV) to student learning, this paper provides descriptive analysis of the nature, prevalence of GBV experienced by students attending secondary education in Morogoro Municipal Council, and emerging issues in process of addressing institutional gaps that fuels GBV. This cross-sectional study selected at randomly both, three secondary schools and student participants attending those secondary school located at MMC in Tanzania. Data were collected through a well-structured interview schedules and questionnaires. The study utilized descriptive statistics in the analysis school-related GBV pattern. The study’s findings revealed that physical, psychological, sexual, gender and health based violence are becoming recurring decimal in the hall-mark of students learning in secondary schools. However, physical violence and psychological violence accounted for the bulk of violence against children in schools. This paper concludes that profiling the pattern of school-related GBV provides socio-dynamic means of addressing the problem. The study ends by recommending a need to review Tanzania’s educational policy of 2014 to accommodate dimensions of school-related GBV.